1998
DOI: 10.1046/j.1432-1327.1998.2530076.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity of two caspases related to interleukin‐1β‐converting enzyme

Abstract: Interleukin-1β-converting enzyme is a member of a family of human cysteine proteases with specificity for aspartic acid, which have been named caspases. Within this family of enzymes, transcript X (TX) and transcript Y (TY) (caspases 4 and 5, respectively) are very similar to ICE (caspase 1) and form the ICE subfamily. Given the high degree of conservation in the sequences of these proteases (more than 50% amino acid identity in the mature enzymes), it was of interest to examine whether they shared similar sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…By contrast, caspase-4 dependent IL-18 processing and secretion appears to be independent of caspase-1 in human IECs. Caspase-4 is able to cleave IL-18 (Fassy et al, 1998), at the same processing site as human caspase-1 (Gu et al, 1997), which might account for our findings. These distinctive features suggest there are mechanistic differences in non-canonical inflammasome activation between myeloid-derived cells and epithelial cells.…”
Section: Discussionsupporting
confidence: 51%
“…By contrast, caspase-4 dependent IL-18 processing and secretion appears to be independent of caspase-1 in human IECs. Caspase-4 is able to cleave IL-18 (Fassy et al, 1998), at the same processing site as human caspase-1 (Gu et al, 1997), which might account for our findings. These distinctive features suggest there are mechanistic differences in non-canonical inflammasome activation between myeloid-derived cells and epithelial cells.…”
Section: Discussionsupporting
confidence: 51%
“…Caspase-1 is unequivocally required for the proteolytic processing of pro-IL-1β and pro-IL-18 and for pyroptosis in response to canonical inflammasome activators23458910. Caspase-11 cannot directly proteolytically process pro-IL-1β and pro-IL-1861, although previous studies suggest that one of the caspase-11 homologs in humans, caspase-4, could cleave pro-IL-1β and pro-IL-186263. Caspase-11 itself is capable of driving pyroptosis in a caspase-1–independent manner in response to non-canonical activation of the inflammasome, that is, in response to transfection of LPS or during infection by certain Gram-negative bacteria, including C. rodentium, E. coli and Vibrio cholerae 16.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated that caspases 4, 5 and 11 activate the NLRP3 inflammasome in response to Gram-negative bacteria and intracellularly-delivered lipopolysaccharide (LPS), placing caspases 4, 5 and 11 as activators of caspase 1 to promote caspase 1-dependent cleavage of IL-1β and IL-18 (Refs 29, 32-41 ). Direct cleavage of IL-1β and IL-18 by caspase 4 has been proposed 42, 43 , but further study is required to confirm this observation. Activation of caspases 4, 5 and 11 also leads to pyroptosis, and the release of IL-1α and the alarmin high-mobility group protein 1 (HMGB1) independently of caspase 1 (Refs 29, 32-39, 44, 45 ).…”
Section: Inflammatory Caspases and The Inflammasomementioning
confidence: 97%